Asepsis / protection washing hands (New York : Insight Media, 1992)
Emphasizing the importance of hand washing for the prevention of infection, this program shows the three minute and the 30-second hand wash. It illustrates the recommended produce for washing, rishing, and drying hands
ABC-11
Keywords: Asepsis